A Photoresponsive Surface Covalent Organic Framework: Surface‐Confined Synthesis, Isomerization, and Controlled Guest Capture and Release. Issue 20 (31st March 2016) - Liu, Chunhua; Zhang, Wei; Zeng, Qingdao; Lei, Shengbin
Abstract: By introducing an azobenzene group to the backbone of diboronic acid, we have obtained a surface‐confined, photoresponsive single‐layer covalent organic framework with long‐range order and almost entire surface coverage. Scanning tunneling microscopic characterization indicates that though the covalent linkage provides a significant locking effect, isomerization can still happen under UV irradiation, which causes destruction of the surface COF. Furthermore, the decomposed surface COF can recover upon annealing. This photoinduced decomposition provides a facile approach for the controlled capture and release of targeted objects using these nanoporous surface COFs as a host, which has been demonstrated in this work using copper phthalocyanine as a model guest. Abstract : A photosensitive surface COFABBA is successfully synthesized by using azobenzene‐linked 4, 4′‐phenylazobenzoyl diboronic acid (ABBA) at the gas/HOPG interface. The reversible photoinduced decomposition‐recovering of the surface COF offers a new method for the controlled capture and release of target objects (see scheme).